Workplace discrimination and its relationship with organizational commitment among the surgical technologist: A national cross-sectional study in Iran - Teymoori, Esmaeil; Shahkarami, Negar; Ghanavati, Maryam; Maleki, Zahra; Fereidouni, Armin (Frontiers in Psychology, 2023)
Background: Discrimination in healthcare centers can reduce care quality and job satisfaction, weaken the morale of the personnel and increase the cost of health care and finally lead to turnover intention. Discrimination in hospitals can affect the work outcomes and performance indicators of nurses such as their organizational commitment. Due to the vital role of surgical technologists in surgery and justice as the basis of effective performance, as well as the role of organizational commitment in care quality, the present study was conducted aimed to determine the level of workplace discrimination from viewpoint of the surgical technologists and its relationship with the organizational commitment. Methods: This cross-sectional study was conducted on 615 surgical technologists in 8 metropolises of Iran in 2022. The sampling method in this study was multi-stage. The data collection tools included three questionnaires (demographic information, workplace discrimination, and Allen and Meyer's organizational commitment). Data were collected within 2 months and analyzed by SPSS version 22. Descriptive and inferential analyzes including independent t-test and analysis of variance were used for data analysis. P-value ≥0.05 was considered significant. Results: The average age of the participants in the study were 29.90±5.83 years with the participation of 464 women. The results of the data analysis showed an inverse and significant correlation between workplace discrimination and organizational commitment (r=-0.149, P-value<0.001). The mean and standard deviation for workplace discrimination was 108.20±11.53, which is average. Also, the mean and standard deviation for total organizational commitment was 100.56±19.14, which is higher than the average. Conclusion: According to the results of this study, managers need to pay attention to reduce discrimination in the operating room and establish organizational justice, to improve the motivation of surgical technologists and the quality of their performance. It is also suggested that operating room managers and supervisors, by creating a safe, confidential, and fearless environment to encourage the personnel to express what they understand about discriminatory conditions.